Management of the Distal Ureter During Nephroureterectomy for Upper Tract Urothelial Carcinoma: A Comprehensive Review of Literature - Morriss, Samuel; Zargar, Homayoun; Dias, Brendan Hermenigildo (Urology Journal, 2021)
Purpose: Radical open nephroureterectomy (ONU) with bladder cuff excision (BCE) is the traditional gold standard approach for management of high-risk non-metastatic upper tract urothelial cancer. ONU involves two separate procedures; the nephrectomy and distal ureterectomy, with each of these parts being able to be performed with an open or minimally-invasive approach. Multiple approaches have been described for the resection of the distal ureter and bladder cuff after mobilization of the kidney and upper ureter. Materials and Methods: A Medline search of the literature including relevant articles up to March, 2020 was performed. Search terms included “nephroureterectomy”, “upper tract urothelial carcinoma”, “upper urinary tract carcinoma OR UTUC”, “open OR conventional OR ONU OR conventional”, “robotic-assisted nephroureterectomy OR RANU”, “laparoscop* OR LNU OR LRNU” and “minimally-invasive nephroureterectomy”. Original articles, case series and review articles were included. Results: There are no randomised studies. Various techniques have been described to manage the distal ureter during nephroureterectomy. This review provides an overview of these techniques. The perioperative and oncological outcomes following open versus endoscopic techniques and minimally invasive techniques have been described. Although endoscopic approaches have more favourable perioperative outcomes, this comes at the expense of increased risk of tumour spillage and recurrence compared to the traditional open approaches. Minimally-invasive techniques (laparoscopic and robotic-assisted NU) largely have superior perioperative outcomes versus their open NU counterparts, with comparable oncological outcomes. Conclusion: Current non-randomised evidence is open to selection bias and is insufficient to support or refute endoscopic management of the distal ureter as an alternative to open bladder cuff excision. The optimal approach to nephroureterectomy and management of the distal ureter continues to remain a surgical dilemma.